EFFECT OF INBREEDING ON PREWEANING GROWTH TRAITS AND SURVIVAL RATE IN SAKIZ SHEEP - A. Ceyhan; A. Kaygisiz; T. Sezenler (Journal of Animal and Plant Sciences, 2011)
The objective of this study was to estimate the effect of inbreeding on birth weight (BW), weaning weight (WW90), and lamb survival rate (LSR) in Sak?z sheep. The effect of inbreeding on BW, WW90, and LSR traits was studied by analysis of variance technique and regression method. Inbreeding had a significant effect on BW and the regression coefficient of inbreeding on BW was -0.0245±0.0076 kg (P<0.01). The mean level of inbreeding (F) of all animals overall years was 2.25% for lambs. The inbred lambs rate was 17.7%. The coefficient of inbreeding ranged from 6.25% to 25.0% and average was 12.68% for birth weight in inbred lambs. Inbreeding weren't a significant effect on weaning weight at 90 days of age and lamb survival rate. It was concluded that inbreeding showed deleterious effects on birth weight and had a no effect on lamb's weaning weight and survival rate.
Keywords: Inbreeding; Sak?z sheep; Preweaning growth; Lamb survival